2014
DOI: 10.1002/ejoc.201301741
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Conformational Study of Model Peptides Containing N‐Substituted 3‐Aminoazetidine‐3‐carboxylic Acids

Abstract: Model peptides containing N‐substituted 3‐aminoazetidine‐3‐carboxylic acids have been synthesized to investigate the conformational features of these Cα‐tetrasubstituted amino acids. The target peptides were designed and prepared by classical synthetic methods in solution, exploiting the convenient N‐substituted 3‐azidoazetidine‐3‐carboxylic acids as precursors. The conformational preferences of the newly synthesized peptides were investigated in solution by IR and NMR spectroscopy. It was observed that the 3‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…IR spectroscopy has been widely used to analyze hydrogen bonding due to the sensitivity of the CO and N–H stretching frequencies of the amides to the hydrogen-bonding behavior. In general, a large red shift of the ν­(CO) (amide I, 1600–1800 cm –1 ) and ν­(NH) (amide A, 3300–3500 cm –1 ) frequencies was observed upon their participation in hydrogen bonding. …”
Section: Resultsmentioning
confidence: 97%
“…IR spectroscopy has been widely used to analyze hydrogen bonding due to the sensitivity of the CO and N–H stretching frequencies of the amides to the hydrogen-bonding behavior. In general, a large red shift of the ν­(CO) (amide I, 1600–1800 cm –1 ) and ν­(NH) (amide A, 3300–3500 cm –1 ) frequencies was observed upon their participation in hydrogen bonding. …”
Section: Resultsmentioning
confidence: 97%
“…To demonstrate the usefulness of the synthesized constrained C α ‐tetrasubstituted amino acid derivative 20 as a possible building block for the synthesis of peptides, it was subjected to hydrogenolysis and hydrolysis reactions 1c,21. The hydrogenolysis of 3‐azidoazetidine 20 by using 10 wt.‐% palladium on carbon in ethanol at room temperature for 30 min afforded ethyl 1‐tosyl‐3‐aminoazetidine‐3‐carboxylate ( 22 ) in 83 % yield.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, our research group reported the synthesis of azetidines 5 , which are heterocyclic analogues of amino acid 4 and have an electron‐donating alkyl group at the azetidine nitrogen atom (Figure 3). 1c A subsequent investigation of the conformational features of these amino acid analogues in model peptides 6 and 7 led us to conclude that such a 3‐aminoazetidine‐3‐carboxylic acid moiety is a β‐turn inducer 21…”
Section: Introductionmentioning
confidence: 99%
“…In general, azetidines are considered the most difficult of all to form . Azetidines have excellent physicochemical properties, bioavailability and metabolic stability. A wide variety of antibiotics, numerous anticancer agents , containing azetidines, and other drug molecules have been developed over the last decade. ,− They have a significant role as synthetic building blocks of foldamers, , N -heterocycles, and polymers . It has also been demonstrated, that the introduction of these strained rings improves enormously the fluorescent properties of rhodamines and coumarins and the efficacy of homogenous catalysts as ligands, , which makes them an attractive and challenging synthetic topic for chemists nowadays.…”
Section: Introductionmentioning
confidence: 99%